2010
DOI: 10.1371/journal.pone.0014335
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors Downregulate Checkpoint Kinase 1 Expression to Induce Cell Death in Non-Small Cell Lung Cancer Cells

Abstract: BackgroundHistone deacetylase inhibitors (HDACis) are promising anticancer drugs; however, the molecular mechanisms leading to HDACi-induced cell death have not been well understood and no clear mechanism of resistance has been elucidated to explain limited efficacy of HDACis in clinical trials.Methods and FindingsHere, we show that protein levels of checkpoint kinase 1 (Chk1), which has a major role in G2 cell cycle checkpoint regulation, was markedly reduced at the protein and transcriptional levels in lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 38 publications
5
51
0
Order By: Relevance
“…To confirm that loss of ING2 did lead to gene repression, we validated some target genes with real-time PCR. We chose to focus on CDC2 because it is a master regulator of G2/M phase cell cycle progression and its protein levels are known to be reduced by HDAC inhibitors in some cell lines (44). We found that CDC2 was consistently down-regulated in ING2 knockdown cells and repressed by SAHA treatment (Fig.…”
Section: Fig 3 Saha-induced Differential Network Analysismentioning
confidence: 99%
“…To confirm that loss of ING2 did lead to gene repression, we validated some target genes with real-time PCR. We chose to focus on CDC2 because it is a master regulator of G2/M phase cell cycle progression and its protein levels are known to be reduced by HDAC inhibitors in some cell lines (44). We found that CDC2 was consistently down-regulated in ING2 knockdown cells and repressed by SAHA treatment (Fig.…”
Section: Fig 3 Saha-induced Differential Network Analysismentioning
confidence: 99%
“…Histone deacetylase (HDAC) modulates the transcription rate and the protein levels of several components of the DNAdamage response cascade [109][110][111][112][113][114]. Heat-shock protein 90 (HSP90) chaperones "client" proteins into their native conformations, regulating multiple aspects of protein function.…”
Section: Heat Shock Protein 90 and Histone Deacetylase Inhibitorsmentioning
confidence: 99%
“…Increased accessibility to DNA-damaging agents, however, is unlikely to be the only mechanism responsible for the effects of treatment with HDAC inhibitors. HDACs have also been shown to regulate the transcription rate and the protein levels of several components of the DDR cascade (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Hdac Inhibitors and The Dna Damage Responsementioning
confidence: 99%